Variations in the enzymatic behaviour of irradiated epidermis as function of age and lesion localization - Frasch, Carlos Alberto; Itoiz, María E. (Taylor & Francis, 1977)
Fil: Frasch, Carlos Alberto Comisión Nacional de Energía Atómica; Argentina